The canonical Hebrew Bible : a theology of the Old Testament - Rendtorff, Rolf, 1925-2014. (Tools for Biblical Study, 2005)
Founded on a lifetime's research and creative thought, this is the crowning work of an internationally celebrated Hebrew Bible/Old Testament scholar. Part I provides an engaging running commentary on the text from a final-form, canonical perspective, and Part II deals with a range of thematic issues, including: creation, covenant and election, the patriarchs, the promised land, torah, cult, Moses, David, Zion, language about God, prophecy, wisdom, Israel's historical consciousness, hermeneutics, Jewish and Christian theology of the Hebrew Bible. It is both an invaluable tool for students and a significant work demanding the attention of professionals.